STRATEGI PEMBANGUNAN PERKOTAAN BERKELANJUTAN DI KOTA BATU - Rama Permana Putra; Agustina Nurul Hidayati; Ida Soewarni (Sekolah Tinggi Pariwisata Mataram, 2021)
The Problems of urbanization and sustainable development has become a global issue and got a lot of attention from stakeholders in various countries. The local government is the most sense due to urbanization and uncontrolled development problems. Batu City is the youngest autonomous city in East Java province increased economic development and the city's population rapidly. The growth of investment flows into the positive signal that can move the real economy and increase the Gross Regional Domestic Product (GRDP). Increased economic activity is suspected as the cause of the degradation of the ecological environment. The geographical location that is located in the upper Brantas river and has a predominance of steep topography severely limits the capacity of the environment of Batu City. This study aims to determine the status of sustainable development in Batu City based on the dimensions ecological, economic, socio - cultural, infrastructural, and institutional. While the output of this research is to improve the status of the sustainability strategy of urban development in Batu. This type of analysis used is included, the analysis of the sustainability of urban development include; leverage analysis, monte - carlo analysis and analysis of Multi - Dimensional Scaling (MDS) analysis to formulate a strategy and development policy analysis using Participatory Prospective Anlysis (PPA). The results showed that the sustainability status of urban development in Batu City is sustainable enough with the sustainability index of 62.89%. Sensitive factors to the sustainability index include: forest conservation, organic agriculture, water resource, water quality, air quality, per capita income, price stability, tourism visitation, SME growth, purchasing power, employment, gender equality, political participation, security, poverty, education, sanitation, appropriate housing, clean water, electricity coverage, public services, local budgets, information systems, and local apparatus. The effective sustainability strategy is the improvement of government services is primed to attract investment in tourism and green economy by empowering small and medium enterprises as well as managing the environment.